Analisis Inovasi Transaksi Uang Kayu dan Dampaknya Pada Pengelolaan Modal Kerja di Pasar Tumpah Pringgodani Balikpapan - Nur Janah; Monika Handayani (P3M Politeknik Negeri Banjarmasin, 2025)
Innovation in transaction systems in traditional markets represents an adaptive response to the dynamics of trading activities that demand efficiency and flexibility. One such innovative phenomenon is the use of wooden money at the Tumpah Pringgodani Market in Balikpapan, a wooden token that serves as a temporary means of payment for small-value transactions. This study aims to analyze the form, mechanism, and implications of wooden money use on traders' working capital management by utilizing secondary data sourced from news articles, video documentation, social media content, and relevant academic literature. The research method used is a descriptive qualitative approach through desk research techniques, which involves the systematic collection, selection, verification, and interpretation of secondary data. The results indicate that wooden money plays a role in expediting transactions, improving operational smoothness, and helping traders manage daily cash flow more stably. However, this practice also has limitations, including the lack of formal recording standards, the potential for calculation errors, and a high dependence on trust among market participants. Overall, the use of wooden money can be seen as an effective local innovation in supporting working capital management, although strengthening administrative mechanisms is needed to ensure its implementation is more accountable and sustainable.